2010
DOI: 10.4028/www.scientific.net/amm.37-38.1482
|View full text |Cite
|
Sign up to set email alerts
|

The Influence Rules of Stress about Technical Parameters on Synchronous Rolling Railway Axis with Multi-Wedge Cross-Wedge Rolling

Abstract: Multi-wedge synchronous rolling by cross-wedge rolling is one of the most advanced methods that can form rolling railway axis. Its rolling quality mainly lies on inner transversal stress and shearing stress of rolling workpiece. In this paper, based on the rotated theory of multi-wedge rolling, through using Ansys/Ls-Dyna FEM software, multi-wedge synchronous rolling railway axis by cross-wedge rolling is simulated. It has been systemically researched that technical parameters effect transversal stress and she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 3 publications
0
18
0
2
Order By: Relevance
“…However, the conducted research works [8,9] showed that realization of this rolling case would require constructing a rolling machine of large dimensions (wedge diameter would be 1.6 m) and power. Hence, searching for new, effective ways of rail axles forming, which are nowadays manufactured from free forged forgings, is still up-to-date issue.…”
Section: Introductionmentioning
confidence: 99%
“…However, the conducted research works [8,9] showed that realization of this rolling case would require constructing a rolling machine of large dimensions (wedge diameter would be 1.6 m) and power. Hence, searching for new, effective ways of rail axles forming, which are nowadays manufactured from free forged forgings, is still up-to-date issue.…”
Section: Introductionmentioning
confidence: 99%
“…375 mm) using tools, the maximum length of which could not exceed 1250 mm (their maximum length was due to the machine design). For that reason, we decided to employ multi-wedge rolling that is also used for producing elongated parts such as stepped axes and shafts [16][17][18][19]. To this end, we designed tools with three wedges described by the same forming angles set to 25°.…”
Section: Numerical Modeling Of the Proposed Process For Forming Ballsmentioning
confidence: 99%
“…The research and development works conducted so far have concentrated on the application of this method for producing automotive axle shafts [2,[5][6][7], stepped shafts [4,8] as well as railway axles, both solid [9] and hollow [3]. In addition to this, the method can be used for forming several short parts at one time.…”
Section: Survey Of the Research On Mwcrmentioning
confidence: 99%